Change paradigm of money system: from centralization to decentralization - S. A. Andryushin (Russian Journal of Economics and Law, 2018)
Objective: to consider the features of centralized and decentralized monetary systems development and to identify the necessary conditions for the transition of the national economy to decentralized network platforms operating within the distributed ledger technology, public and private digital currencies.Methods: a systemic approach to the cognition of economic phenomena, enabling to study them in dynamic development, taking into account the influence of various environmental factors. The systemic approach determined the choice of specific research methods: empirical, historical, logical, comparative and statistical.Results: the article considers different approaches to the organization of money issue. It is shown that the era of the centralized monetary system, based on the issue of Central banks, has come to its end. The Central bank is the main link of the centralized monetary system, while in the context of 2008 financial crisis the functions of the Central Bank as the lender of last resort were significantly expanded by changing the paradigm of the monetary mechanism. It is established that the new monetary mechanism has become the main channel of money supply in the economy, while the main factors of the new monetary supply formation are the reserve money of Central banks, new Basel standards and high requirements for borrowers. This monetary policy and the centralization of the financial market have led to a distortion of the market pricing mechanism in the monetary market and to the disruption of competition in the financial intermediation market. The author analyzes the new trends in the emergence of a decentralized monetary system in the world economy based on public and private digital currencies issued by users of distribution computer networks. The article shows the mechanism and technology of crypto currency emission, which implies the use of public or private blockchain without any participation of the Central bank and other financial intermediation institutions.Scientific novelty: for the first time, the article shows that the era of centralized monetary system based on monopoly issue by Central banks, has come to its logical end; a decentralized monetary system is emerging in the world economy today, based on public and private issue of digital currency; in the course of legalization, growth of scalability, confidentiality, validation and tokenization of real assets, the crypto currencies will become a liquid and less volatile monetary asset.Practical significance: the main provisions and conclusions of the article can be used to clarify the target mandates, tools, channels and mechanisms of monetary policy of the Bank of Russia, capable of launching a decentralized crypto currency market, acting as a built-in stabilizer of financial sustainability and elastic regulation of trade and financial imbalances within the country and between countries.